2014
DOI: 10.1002/ejic.201402220
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Control of Biomimetic Coordination – ZnII Cavity Complexes Presenting Two Differentiated Labile Sites in cis Positions

Abstract: A supramolecular approach to model the active sites of metalloenzymes is to associate a cavity with a tripodal coordination core. One key feature of many enzymes is the possible binding of two different ligands in cis positions relative to each other, which has not yet been described for cavity complexes. Here, the bowl shape of resorcinarene allows such a coordination environment for Zn II complexes. A detailed NMR study with various carboxylic acids evidences size-, shape-, and, thus, regioselectivity for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The binding site of the receptor is thus expandable, as previously observed for Rim 3 . [19] The presence of only two resonances for the coordinating imidazole moieties in the aromatic region indicates that the imidazole arms are flippingq uickly( relative to the NMR chemicals hift time scale) from ac oordinated state to an uncoordinated one, as previously observed for Rim 4 in MeCN.…”
Section: Acetylacetonatesupporting
confidence: 52%
See 1 more Smart Citation
“…The binding site of the receptor is thus expandable, as previously observed for Rim 3 . [19] The presence of only two resonances for the coordinating imidazole moieties in the aromatic region indicates that the imidazole arms are flippingq uickly( relative to the NMR chemicals hift time scale) from ac oordinated state to an uncoordinated one, as previously observed for Rim 4 in MeCN.…”
Section: Acetylacetonatesupporting
confidence: 52%
“…[18] This has been attributed to electrostaticr epulsion by the oxygen-rich narrow rim as as econd coordination sphere.I nc ontrast, rigid bowlshaped resorcinarene-based metal complexes,o fferingav ery differentsecond coordination sphereand shape, display strong affinity towards small anionic guests. [19] Our most recently described bowl complex,b ased on the new ligand Rim 4 , [20] is depicted in Scheme 1. In this system, the resorcinarene is functionalized at its large rim with four imidazole arms,t hree of which firmly hold the Zn II ion at the entrance of the bowl-shaped cavity,w hereast he fourth is hemilabile.…”
Section: Introductionmentioning
confidence: 99%
“…With Rim 3 , it was shown that the Zn II center displays very strong affinity for this guest provided a base (triethylamine) was added to the solution, leading to the formation of the monocationic [ Rim 3 Zn(OAc)] + adduct. 33 Having evidenced the lability of the fourth imidazole arm of complex [ Rim 4 Zn(MeCN)] 2+ mediated by the addition of a strong acid, we explored the possible concomitant deprotonation/coordination of AcOH by the complex based on Rim 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The three associated dicationic acetato complexes actually correspond to different solvated forms. Indeed, we have previously shown that the analogous tris(imidazole) Zn II complex, based on the Rim 3 ligand, 33 can bind exogenous donors in the exo position, such as solvent (MeCN) or residual water. Here, the protonation of one imidazole arm opens a coordination site in the exo position that can be free (major species under these experimental conditions {[ Rim 4 HZn(OAc)] 2+ }, or occupied by solvent or residual water {[ Rim 4 HZnS(OAc)] 2+ }).…”
Section: Resultsmentioning
confidence: 99%
“…This biomimetic strategy led us to develop the concepts of funnel and bowl complexes, based on the calix[6]arene and resorcin[4]arene scaffolds, respectively. Whereas the latter presents strong affinities for organic anions, the funnel complexes display remarkable guest recognition properties for neutral molecules having a Lewis base available for metal‐ion coordination. The recognition pattern of the calix[6]‐based funnel complexes is highly selective towards primary amines vs. secondary and tertiary due to the narrowness of the small rim (Figure a) .…”
Section: Introductionmentioning
confidence: 99%